2016
DOI: 10.17267/2238-2720revbahianaodonto.v7i2.874
|View full text |Cite
|
Sign up to set email alerts
|

Manejo Clínico Multidisciplinar Da Reabilitação Estética Utilizando Cerâmicas Puras: Revisão De Literatura

Abstract: ResumoO anseio por um sorriso estético e harmônico eleva o nível de exigência e de expectativa do paciente devido o indivíduo estar inserido numa sociedade onde a aparência tem grande relevância na sua aceitação e autoestima. Dentro desse contexto, uma abordagem multidisciplinar para a reabilitação estética e funcional do sorriso foi inserida na Odontologia contemporânea, destacando-se tratamentos mais conservadores como o clareamento dentário, o aumento de coroa clínica, coroas e facetas cerâmicas por meio de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
0
0
Order By: Relevance
“…Studies have reported that some people do not realize the need for orthodontic treatment until they receive a dentist's recommendation [4]. Analyzing the results of the studies, the authors agreed that it is necessary to understand how individuals perceive their treatment needs and the impact of their day-to-day activities, because in this way, it is possible to establish priorities in orthodontic treatment [4,30].…”
Section: Silva Et Al [31]mentioning
confidence: 99%
“…Studies have reported that some people do not realize the need for orthodontic treatment until they receive a dentist's recommendation [4]. Analyzing the results of the studies, the authors agreed that it is necessary to understand how individuals perceive their treatment needs and the impact of their day-to-day activities, because in this way, it is possible to establish priorities in orthodontic treatment [4,30].…”
Section: Silva Et Al [31]mentioning
confidence: 99%